2014
DOI: 10.1126/science.1252884
|View full text |Cite
|
Sign up to set email alerts
|

Composition of isolated synaptic boutons reveals the amounts of vesicle trafficking proteins

Abstract: Fig. S6Tables S1 to S3 (as Excel files) Movie S1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
706
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(752 citation statements)
references
References 47 publications
41
706
2
3
Order By: Relevance
“…The physiological concentration of α-synuclein in neuronal synapses is estimated to be about 50 μM (27,28), a concentration of protein that can be studied by NMR spectroscopy (27,(29)(30)(31)(32). We therefore used this technique to probe potential interactions between α-synuclein and squalamine in the absence of lipids and to characterize the displacement of the protein from lipid membranes by squalamine, as suggested by the CD experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological concentration of α-synuclein in neuronal synapses is estimated to be about 50 μM (27,28), a concentration of protein that can be studied by NMR spectroscopy (27,(29)(30)(31)(32). We therefore used this technique to probe potential interactions between α-synuclein and squalamine in the absence of lipids and to characterize the displacement of the protein from lipid membranes by squalamine, as suggested by the CD experiments.…”
Section: Resultsmentioning
confidence: 99%
“…These lipids have the characteristic feature of a large polar head that can increase their solubility in aqueous solution (1-30 μM for GM1) (11,45,46). It is interesting in this regard that the presence of transmembrane and peripheral proteins in synaptic vesicles is also likely to modulate the efficiency of α-synuclein binding to the vesicles, and hence their capacity to enhance protein aggregation (38,47).…”
Section: Discussionmentioning
confidence: 99%
“…37 Comparison of synaptosomal proteins with proteins in undisturbed brain slices has shown that synaptic bouton protein composition is maintained in synaptosomes. 41 Demographic and neuropathologic data for the normal control, HPC, and AD cases are shown in Table 1. HPCs indicated substantial Ab and/or tau pathology but did not meet clinical criteria for dementia.…”
Section: Total In Situ Synaptic Ab Is Associated With Plaque Level Inmentioning
confidence: 99%